Advancing syphilis diagnosis: multi-phase study evaluation of a TpN17-based double-antigen sandwich ELISA for detecting Treponema pallidum specific antibodies - Silva, Ângelo Antônio Oliveira; Vasconcelos, Larissa Carvalho Medrado; Freitas, Natália Erdens Maron; Oliva, Talita Andrade; Silva, Miralba Freire Carvalho Ribeiro; Siqueira, Isadora Cristina; Silva, Edimilson Domingos; Santos, Keila Gisele Azevedo Figueiredo; Lima, Maria Amélia Virgens; Zanchin, Nilson Ivo Tonin; Santos, Fred Luciano Neves (Frontiers in Microbiology, 2025)
Syphilis, a sexually transmitted infection caused by the bacterium Treponema pallidum, has high incidence rates among adults, pregnant women, and newborns. Diagnostic procedures typically involve a treponemal test (such as ELISA, CMIA, and IFI), followed by a non-treponemal test (VDRL and RPR). This study aimed to assess the diagnostic performance of a double antigen sandwich ELISA (DAgS-ELISA) using the recombinant protein TpN17, analyzing serum samples from both infected and not infected with T. pallidum. A total of 712 samples were deemed eligible and recharacterized using VDRL, ELISA, and FTA-ABS, with 613 ultimately included in the evaluation: 180 T. pallidum-positive, 169 T. pallidum-negative, and 264 positive samples for other diseases. The assay was standardized using checkerboard titration and evaluated based on the area under the ROC curve (AUC), sensitivity, specificity, accuracy, likelihood values, diagnostic ratio, and Cohen’s Kappa index (κ). In phase I, positive and negative samples showed statistical differences (p < 0.0001) for the TpN17 protein. The ROC curve (AUC) was 98.7% and Cohen’s Kappa of 0.91, indicating almost perfect agreement with the reference tests. Phase II results demonstrated an AUC of 97.5%, specificity of 100%, sensitivity of 88.9%, accuracy of 94.3%, a positive likelihood ratio of 1.512, a negative likelihood ratio of 0.11, and a diagnostic odds ratio of 13,600, with a Cohen’s Kappa of 0.89. Cross-reactivity was observed in samples positive for Chagas disease (11.5%), HBV (2.6%), HCV (6.4%), and HTLV-1/2 (6.8%). Overall, TpN17 exhibited high diagnostic performance across all clinical stages of syphilis. Future research should expand the sample panel and explore new proteins to enhance DAgS-ELISA’s effectiveness and applicability for syphilis diagnosis across diverse clinical settings.